Systematic review and meta-analysis of frailty as a predictor of morbidity and mortality after major abdominal surgery. Issue 5 (9th November 2017) - Sandini, M; Pinotti, E; Persico, I; Picone, D; Bellelli, G; Gianotti, L
Abstract: Background: Frailty is associated with poor prognosis, but the multitude of definitions and scales of assessment makes the impact on outcomes difficult to assess. The aim of this study was to quantify the effect of frailty on postoperative morbidity and mortality, and long-term mortality after major abdominal surgery, and to evaluate the performance of different frailty metrics. Methods: An extended literature search was performed to retrieve all original articles investigating whether frailty could affect outcomes after elective major abdominal surgery in adult populations. All possible definitions of frailty were considered. A random-effects meta-analysis was carried out for all outcomes of interest. For postoperative morbidity and mortality, overall effect sizes were estimated as odds ratios (OR), whereas the hazard ratio (HR) was calculated for long-term mortality. The potential effect of the number of domains of the frailty indices was explored through meta-regression at moderator analysis. Results: A total of 35 studies with 1 153 684 patients were analysed. Frailty was associated with a significantly increased risk of postoperative major morbidity (OR 2·56, 95 per cent c.i. 2·08 to 3·16), short-term mortality (OR 5·77, 4·41 to 7·55) and long-term mortality (HR 2·71, 1·63 to 4·49). All domains were significantly associated with the occurrence of postoperative major morbidity, with ORs ranging from 1·09 (1·00 to 1·18) for co-morbidity to 2·52 (1·32 to 4·80) for sarcopenia. No moderator effect was observed according to the number of frailty components. Conclusion: Regardless of the definition and combination of domains, frailty was significantly associated with an increased risk of postoperative morbidity and mortality after major abdominal surgery. Graphical Abstract: We ran a random-effect meta-analysis to evaluare the effect of frailty on morbidity and postoperative mortality. A total of 35 studies with 1 135 300 patients were analysed. Frailty was associated with a significantly increased risk of postoperative major morbidity, short-term mortality and long-term mortality. Frailty increases morbidity and mortality